Addressing Health, Social, and Economic Inequalities Through Sport and Social Care Partnership (Baltic Journal of Sport and Health Sciences, 2026)
Community Integrated Care delivers 8 million hours of care and support for people with learning disabilities, autism, mental health concerns, and age-related needs across the United Kingdom.It has formed a unique ‘Social Care Partner’ (SDG17) model with leading sports, including Rugby League and British Cycling, and major tournaments, to create radical physical-activity and support solutions that address health, social, and economic inequalities in care (SDG1, 4, 8, 10).The charity fights inequalities faced by people with complex needs – including a 20+ year gap in life-expectancy for people who have learning disabilities, a 96% unemployment rate, face rising disability hate crime and a disabling society.The charity’s specialist Sports Inclusion function applies its specialist infrastructure and experience to empower major sports and tournaments to address these inequalities. Through co-production with the sports and the excluded community, mapping assets and aligning missions, they have delivered transformational solutions, including:•          Variants of major sports for people with learning disabilities: These twin physical activity with specialist personal development and support. Their learning disability variant of rugby league’s ‘Super League’ is assessed by Manchester Met Uni as generating 1.39 m EUR of social value annually through transforming physical activity levels whilst empowering mental health, skill, and inclusion.•          Developing social enterprise models and its Inclusive Volunteering Model with events such as UEFA Euro 2022 and World Para Swimming Championships. These support people facing profound health, social, and economic exclusion to become active, learn, and create a pathway to work. This has radically transformed health, life skills, and opportunities (Prof Sam Hook, Substance, 2023: 97% report greater skills and confidence).The partnership model is an unprecedented methodology, leveraging the strengths of both sectors to create sustainable, impactful interventions that transform health. The United Kingdom government’s Skills for Care agency named it as the “Best New Model of Integrated Care”.This approach is inherently sustainable and scalable across borders. The combination of sport and social care drives the commercial and strategic goals of sports and tournaments (awareness, reach, and impact), whilst also relieving financial pressures on stretched care systems through leveraging community assets and taking preventative health approaches.